ASSESSMENT OF THE SKILL COMPETENCY OF BUSINESS EDUCATION STUDENTS IN SELECTED HIGHER INSTITUTIONS IN OGUN STATE - M. B., Amoda; K. O., Odunaike (European Scientific Journal, ESJ, 2014)
Nigeria is currently going through socio-economic and political stress which brings into lime-light the present situation of Nigeria economic development, which has virtually affected the whole system of governance, commerce, industry, judiciary and of course the Educational system. It is obvious that an individual especially students who are subjected to such stress might exhibit low or negative emotion, which may automatically affect their performance. There are various educational programmes aimed at addressing the quality of education which had been continuously alleged to be falling incessantly. It is this research method was employed which involves a structured questionnaire to elicit response from the respondents. Three (3) hypotheses were formulated from the structured questionnaire and chi-square descriptive method was used to analyse it. Two (2) institutions were used in this study, namely; Tai Solarin University of Education (TASUED), Ijagun, Ijebu-Ode and Olabisi Onabanjo University (OOU), Ago-Iwoye. The questionnaire was basically structured and administered by the two (2) researchers, fifty (50) students were employed respectively in the two (2) universities used for the research which is made up of 100 respondents. Both t-test and chi-square (x2) method were adopted for the analysis to show the relationship between the variance of the findings. The tcal for the universities are 6.251 and 5.672 respectively, of which the t-table is 7.814 at 0.05 level of significant. The reliability of the instrument at crombach alpha (α) is between 0.85 to 0.90. The study recommended that constant training seminars and orientation should be organized at all times among the students and lecturers. Modern office equipment such as reprography, computers, data processor machine, fax machine, telex machine and other telecommunication equipment should be part of learning environment to enable the learners acquire the skills needed to be an expert in his field and thereby competent to face any challenges ahead.